Analisis Perbandingan Premi Asuransi Jiwa pada Model Suku Bunga Deterministik dan Stokastik Berbasis Model Vasicek - Indy Pratiwi; Albert Samuel Sinaga; Miftah Asura (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the comparison of life insurance premiums calculated using a deterministic interest rate model and a stochastic model based on Vasicek. Differences in interest rate assumptions are evaluated based on their impact on the Expected Present Value (EPV) and the resulting premium. The deterministic approach uses a constant interest rate of 4.93% based on the average BI Rate for the 2016–2025 period, while the stochastic approach applies the Vasicek model with Monte Carlo simulation to represent interest rate fluctuations. The data used include historical interest rates and the 2019 Indonesian Mortality Table (TMI). The results show that the EPV Benefit in the Vasicek model is 1.16% higher than the deterministic model, which results in a premium increase of 0.36% (Rp 173,592 compared to Rp 172,967). This relatively small difference indicates that the premium sensitivity to interest rate changes in this study is relatively low. This study confirms that the Vasicek model provides more realistic estimates because it captures interest rate dynamics. However, the significance of the differences is significantly influenced by the level of volatility. Therefore, the use of stochastic models in premium determination becomes more relevant in conditions of highly fluctuating interest rates.